Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1002/jcp.1041140308
|View full text |Cite
|
Sign up to set email alerts
|

Neovascular responses induced by cultured aortic endothelial cells

Abstract: Neovascularization was studied in the chorioallantoic membrane of the chick embryo after implantation of bovine aortic endothelial and smooth muscle cells, Swiss and BALB/c 3T3 cells and human diploid fibroblasts cultured separately on microcarrier beads. Quantitative analysis of neovascularization indicated a 3 1/2-fold increase in the number of blood vessels responding to endothelial cells while smooth muscle cells induced a twofold increase when compared to the response of beads without cells. Skin fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…L-NAME (nmol/disc) Figure 4 Effect of increasing amounts of (a) N0-monomethyl-L- Hooker et al (1983) showed that the vascular density under the disc containing 38.7 nmol of dexamethasone increased by 31.5 ± 4.4%, n = 6, P<0.01. At 116.1 nmol/disc, the angiogenic effect of dexamethasone was reduced to 18.2 ± 4.6%, n = 7 and at 348.4 and 1161 nmol/disc it caused a 24.8 ± 9.5%, n = 6 (P<0.05) and 65.0 ± 4.9%, n = 7 (P< 0.01) decrease in collagenous protein biosynthesis ( Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…L-NAME (nmol/disc) Figure 4 Effect of increasing amounts of (a) N0-monomethyl-L- Hooker et al (1983) showed that the vascular density under the disc containing 38.7 nmol of dexamethasone increased by 31.5 ± 4.4%, n = 6, P<0.01. At 116.1 nmol/disc, the angiogenic effect of dexamethasone was reduced to 18.2 ± 4.6%, n = 7 and at 348.4 and 1161 nmol/disc it caused a 24.8 ± 9.5%, n = 6 (P<0.05) and 65.0 ± 4.9%, n = 7 (P< 0.01) decrease in collagenous protein biosynthesis ( Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…The windows were covered and the eggs were incubated until day 11, before assessment of angiogenesis. Therefore, the eggs were flooded with 10% buffered formalin, the discs were removed, and the eggs were kept at room temperature for at least 2 h. A large area around the discs was cut out and placed on a glass slide, and the vascular density index was measured by the method of Harris-Hooker et al [33]. Briefly, a grid containing three concentric circles of 6-, 8-and 10-mm diameter was positioned on the surface of the CAM previously covered by the disc.…”
Section: Cam Assaymentioning
confidence: 99%
“…The application of stereological principles to the analysis of microcirculation represents a useful tool for obtaining quantitative information [22]. Several stereological techniques have been described to quantitate an angiogenic response in the CAM [23][24][25][26]. A VDI was calculated by counting the number of intercepts of vessels with concentric circles of a grid, which was placed over the formalin-fixed CAM, or over a photograph of the excised membranes.…”
Section: Discussionmentioning
confidence: 99%